Drug assessment by a Pharmacy and Therapeutics committee: from drug selection criteria to use in clinical practice - Lozano-Blázquez A; Calvo-Pita C; Carbajales-Álvarez M; Suárez-Gil P; Martínez-Martínez F; Calleja-Hernández MA (Dove Medical Press, 2014)
Ana Lozano-Blázquez,1 Cecilia Calvo-Pita,2 Mónica Carbajales-Álvarez,1 Patricio Suárez-Gil,3 Fernando Martínez-Martínez,4 Miguel Ángel Calleja-Hernández51Pharmacy Department, Hospital de Cabueñes, Gijón, Spain; 2Pharmacy Department, Primary Health Care, Servicio Madrileño de Salud, Dirección Asistencial Oeste, Madrid, Spain; 3Research Unit Área V, Hospital de Cabueñes, Gijón, Spain; 4Responsable del Grupo de Investigación en Atención Farmacéutica, Universidad de Granada, 5UGC Provincial de Farmacia de Granada Instituto de Biomedicina de Granada, Hospital Virgen de las Nieves, Granada, SpainBackground: In Spain, hospital medicines are assessed and selected by local Pharmacy and Therapeutics committees (PTCs). Of all the drugs assessed, cancer drugs are particularly important because of their budgetary impact and the sometimes arguable added value with respect to existing alternatives. This study analyzed the PTC drug selection process and the main objective was to evaluate the degree of compliance of prescriptions for oncology drugs with their criteria for use.Methods: This was a retrospective observational study (May 2007 to April 2010) of PTC-assessed drugs. The variables measured to describe the committee's activity were number of drugs assessed per year and number of drugs included in any of these settings: without restrictions, with criteria for use, and not included in formulary. These drugs were also analyzed by therapeutic group. To assess the degree of compliance of prescriptions, a score was calculated to determine whether prescriptions for bevacizumab, cetuximab, trastuzumab, and bortezomib were issued in accordance with PTC drug use criteria.Results: The PTC received requests for inclusion of 40 drugs, of which 32 were included in the hospital formulary (80.0%). Criteria for use were established for 28 (87.5%) of the drugs included. In total, 293 patients were treated with the four cancer drugs in eight different therapeutic indications. The average prescription compliance scores were as follows: bevacizumab, 83% for metastatic colorectal cancer, 100% for metastatic breast cancer, and 82.3% for non-small-cell lung cancer; cetuximab, 62.0% for colorectal cancer and 50% for head and neck cancer; trastuzumab, 95.1% for early breast cancer and 82.4% for metastatic breast cancer; and bortezomib, 63.7% for multiple myeloma.Conclusion: The degree of compliance with criteria for use of cancer drugs was reasonably high. PTC functions need to be changed so that they can carry out more innovative tasks, such as monitoring conditions for drug use.Keywords: decision-making, drug selection, drug utilization, formulary, neoplasm, Pharmacy and Therapeutics committee